Pengaruh Suctioning Terhadap Peningkatan Saturasi Oksigen Pada Pasien ICU Di Rumah Sakit X - Sari Nasip Sianturi; Ricky Riyanto Iksan; Roza Indra Yeni (Akademi Keperawatan Yarsi Samarinda, 2026)
Impaired airway clearance is a common problem in intensive care unit (ICU) patients that can lead to decreased oxygen saturation. Evidence-based nursing practices, such as suctioning, are essential to ensure the effectiveness of interventions in improving patient oxygenation. Objective: EBN examines the effect of suctioning on increasing oxygen saturation in ICU patients based on an evidence-based nursing practice approach. Methods: This nursing care study used a quasi-experimental design with a pretest–posttest approach. Data were collected using an airway clearance and oxygen saturation (SpO₂) observation sheet. Data were analyzed using a paired t-test to determine differences in pre- and post-intervention values. Results: The airway clearance score decreased from 1.40 to 1.00 after the intervention with a p-value of 0.021, indicating a significant improvement. Conclusion: Suctioning has been shown to be effective in improving airway clearance and oxygen saturation in ICU patients. This evidence-based nursing practice can be used as a guideline for interventions to improve the quality of intensive care nursing services.